1997
DOI: 10.1152/ajpgi.1997.273.2.g508
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a bile acid response element in the cholesterol 7 alpha-hydroxylase gene CYP7A

Abstract: The transcriptional activity of the cholesterol 7 alpha-hydroxylase gene CYP7A is repressed by bile acids. Taurine conjugates of chenodeoxycholate and deoxycholate, but not cholate and ursodeoxycholate, inhibited the CYP7A promoter/luciferase reporter activity in transient transfection assays in Hep G2 cells. A region from nucleotide (nt) -74 to -55 was found to mediate bile acid response. However, deletion of this bile acid response element (BARE-I) enhanced reporter activity but did not eliminate the bile ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
79
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 0 publications
1
79
0
Order By: Relevance
“…63 Because the amount of deoxycholate infused represented only 24% of the cholate dose, a superior suppressive capacity of this more hydrophobic bile acid is likely, at least under physiological conditions. Recent studies in human HepG2 cells support 15,16,64 the role of hydrophobicity for regulation of bile acid synthesis. Our studies in healthy volunteers 19 clearly support such an assumption, although a reduced capability of conjugated cholate uptake in HepG2 cells 15 may have contributed to these observations in this experimental system.…”
Section: Discussionmentioning
confidence: 93%
“…63 Because the amount of deoxycholate infused represented only 24% of the cholate dose, a superior suppressive capacity of this more hydrophobic bile acid is likely, at least under physiological conditions. Recent studies in human HepG2 cells support 15,16,64 the role of hydrophobicity for regulation of bile acid synthesis. Our studies in healthy volunteers 19 clearly support such an assumption, although a reduced capability of conjugated cholate uptake in HepG2 cells 15 may have contributed to these observations in this experimental system.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that the ranking order of bile acid inhibition of bile acid synthetic enzymes is CYP8B1 Ͼ CYP7A1 Ͼ CYP27A1 (11). We have identified previously the bile acid response elements (BAREs) in the CYP7A1, and we proposed a nuclear hormone receptor-mediated mechanism for bile acid feedback inhibition of CYP7A1 transcription (4,13,14). This hypothesis has now been supported by the identification of a nuclear receptor, farnesoid x receptor (FXR), as a bile acid-activated receptor (15)(16)(17).…”
mentioning
confidence: 97%
“…Ligandbound FXR regulates a number of target genes involving BA transport and metabolism (6). BAs also feedback-regulate BA biosynthesis, where activated FXR induces small heterodimer partner (SHP/NR0B2) gene expression, and SHP in turn inhibits liver receptor homolog 1 (LRH-1/NR5A2) or hepatocyte nuclear factor 4␣ (HNF4␣/NR2A1) activities on the BA response elements (BAREs) of CYP7A1 and CYP8B1 promoters (7)(8)(9)(10). BAs can also act via FXR-independent pathways that use PKC (11) and JNK signaling (12,13) to suppress HNF4␣-mediated expression of human CYP8B1 (hCYP8B1) (10,11,14).…”
mentioning
confidence: 99%